The Role of Village Guidance Officers in Increasing Nationalism and Patriotism for 3T Communities (Frontier, Outermost And Disadvantaged) - Rahmat Adi Anggoro; Fauzia Gustarina Cempaka Timur; Ahmad G. Dohamid; Mhd Halkis (CV. AFDIFAL MAJU BERKAH, 2024)
The role of Babinsa in enhancing nationalism and patriotism for the frontier, outermost and underdeveloped communities is an important aspect in building unity and integrity in Indonesia. In their duties, Babinsa have the responsibility to build character, develop local potential, and empower communities to be more independent and developed through mental strengthening and infrastructure development. This research uses qualitative research methods. The results show that Babinsa works closely with local governments, community organisations and the private sector to identify community needs and seek sustainable solutions. This is done in order to improve the quality of life of the community through the provision of entrepreneurship training, local potential development, and assistance to improve welfare. Collaboration between Babinsa, local governments, community organisations and the private sector is the key to success in increasing nationalism and patriotism in frontier, outermost and disadvantaged communities. With synergistic cooperation, awareness of nationalism and love for the country can grow and take root in every individual. In this era of globalisation, the role of the Babinsa is becoming increasingly relevant in shaping the younger generation who have the spirit of nationalism, readiness to face future challenges, and awareness of the importance of national unity